Perlindungan Hukum Nasabah Pada Era Digital : Menyikapi Ancaman Kejahatan Siber Di Sektor Perbankan - Nia Malvin Faradila; Baidhowi (Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
The rapid digital transformation has succeeded in providing significant benefits to the banking world, it is expected to be able to help the banking sector in providing better services to customers and competing with technology in the industry 4.0 era. But besides that, digital transformation also creates a great opportunity for crime risks, such as skimming, phishing, social engineering, and malware that can threaten the security of customers.Therelarelseveral problemlformulations thatiwill beidiscussed inithis article, namely: (1) How do cybercriminals steal customer data in the banking sector? and (2) How is the legal system in overcoming criminal acts of data theft of bank customers? This articlelaims to analyzeihow theirole of currentiregulations in dealing with legalhproblems experienced by the banking world in the digital era.To respond to the formulation of these problems, the author uses normative legal research by covering conceptual approaches, statutory approaches, and collecting data through literature studies.This research is expected to provide useful knowledge to help develop theory and practice in the field of banking digitalization and consumer protection.